Seduhan Jahe Menurunkan Ekspresi TNF α pada Tikus Putih yang Diberi Diet Tinggi Lemak (HFD) - Nurul Mahmudati (Universitas Sebelas Maret, 2016)
Cardiovascular disease still one of the highest death factor in Indonesia. Ginger as an anti-atherosclerosis could be one of the alternatives that are being developed to decrease the cardiovascular disease. The general aims of this research were determining the mechanism of ginger as anti-atherosclerosis to decrease the risk of cardiovascular disease.Research design used was “The Randomized Posttest only Control Group Design”. By this research, the experimental unit was Rattus norvegicus, male; in the age of 3 months and total number were thirty. Independent variable of this research was steeping of ginger, the dose various of steeping ginger (A.control, B. HFD, CHFD+4gZO, 3g + bay leaf, and 5g), and dependent variable was Tumor Necrotic Factor (TNF)α of tissue lipid. TNF α expression was measured by using ELISA method. The data was analyzed by using ANOVA.Based on the analysis, it showed that steeping of ginger was decreased the expression of TNF-α in fat tissue (Control 56,30 113,17 pg/mL, HFD + Exercise 94,30, HFD + Ginger 4 g, HFD + Ginger 6 g 74,33 pg/mL, 3g + bay leaf = 493 pg /mL). Steeping of ginger decreased the risk of TNF α expression that as factor cause of atherosclerosis.Key Word : Ginger, TNF α, aterosklerosis, Cardiovascular